2011
DOI: 10.1039/c0cc02257h
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 1-D nanoparticle superstructures with tailorable thicknesses using gold-binding peptide conjugates

Abstract: We describe the preparation of new 1-D gold nanoparticle superstructures with tailorable thicknesses formed using a self-assembled gold-binding peptide conjugate template and examine how the synthesis and assembly mechanism impacts the organization of the superstructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 18 publications
0
47
0
Order By: Relevance
“…These observations are consistent with our previously reported studies. 26,30 We note that, in this method, in situ nanoparticle growth in the presence of the peptide conjugates is required to achieve ordered nanoparticle assemblies. 26 Cryogenic electron tomography (cryo-ET) was employed to determine the 3-D architecture of the single helices (Figure 2e,f).…”
Section: Resultsmentioning
confidence: 99%
“…These observations are consistent with our previously reported studies. 26,30 We note that, in this method, in situ nanoparticle growth in the presence of the peptide conjugates is required to achieve ordered nanoparticle assemblies. 26 Cryogenic electron tomography (cryo-ET) was employed to determine the 3-D architecture of the single helices (Figure 2e,f).…”
Section: Resultsmentioning
confidence: 99%
“…(12) We demonstrated that these strategies and methods are very useful for targeting, preparing, and tailoring the metrics and structural parameters of a diverse family of 1D gold nanoparticle superstructures, including chiral double helices(12, 25) and linear chains,(26) as well as a collection of discrete hollow spheres consisting of either gold(27, 28) or cobalt–platinum nanoparticles. (29) The precision of nanoparticle placement and the structural integrity of the resulting nanoparticle superstructures are key distinguishing features of this methodology.…”
mentioning
confidence: 99%
“…We successfully demonstrated that this methodology addresses criteria 1 and 2 listed above. Specifically, we used this methodology to prepare a diverse set of complex gold nanoparticle superstructures, including double helices, [2] linear belts, [3] and hollow spherical structures, [4] and to tune the metrics of the superstructures. [5] In this contribution, we begin to address criterion 3 listed above.…”
mentioning
confidence: 99%